The relationship between self-care and quality of life of patients with Chronic Obstructive Pulmonary Disease (COPD) - Ekaputri, Mersi; Ramadia, Arya (Riset Informasi Kesehatan, 2024)
Chronic obstructive pulmonary disease (COPD) is a non-communicable disease that is expected to continue to increase and become one of the causes of death. Improving the quality of life of patients with COPD needs to be considered and improved so that good self-management (self-care) is needed. The purpose of this study was to identify the relationship between selfcare and the quality of life of patients with chronic obstructive pulmonary disease (COPD). Type of quantitative research, correlation design cross sectional approach, research location tenayan raya health center with sampling technique used is purposive sampling with a total sample size of 55 people. The results of the research univariate analysis obtained adequate self-care of COPD patients 56.3%, high quality of life 45.5% the results of bivariate analysis there is a relationship between selfcare with quality of life of COPD patients with p value 0.00. It is hoped that health workers will always pay attention and educate COPD patients about the importance of self-care for COPD patients considering that good self-care by itself can improve quality of life